2020
DOI: 10.1007/s40685-020-00135-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of clawback provisions in management compensation contracts: a structured literature review on empirical evidence

Abstract: The goal of this systematic literature review is to provide a detailed understanding of the determinants and consequences of clawback provisions in management compensation contracts, motivated by the increasing global regulatory, practical, and academic importance of implementing this new corporate governance tool. We identify 44 empirical (archival and experimental) studies on this topic and review them based on an agency-theoretical framework. Our review of empirical clawback research offers insights into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 106 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…Developments following the financial crisis of 2007–2008 have led to institutional changes due to concerns that short-term performance pay fostered incentives for the managers to engage in fraudulent financial reporting. One institutional change has been the rollout of clawback provisions in executive pay that allow for recovery of previously awarded incentive compensation if a financial restatement occurs at the firm [ 43 ]. The Dodd-Frank act mandated such provisions and clawback provisions become increasingly common after 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Developments following the financial crisis of 2007–2008 have led to institutional changes due to concerns that short-term performance pay fostered incentives for the managers to engage in fraudulent financial reporting. One institutional change has been the rollout of clawback provisions in executive pay that allow for recovery of previously awarded incentive compensation if a financial restatement occurs at the firm [ 43 ]. The Dodd-Frank act mandated such provisions and clawback provisions become increasingly common after 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, the presented financial information reduces information asymmetry between the shareholders and managers and ultimately helps investors to build confidence. Velte (2020) in his recent systematic literature review on clawback found that no qualitative work on clawback has been conducted so far. Therefore, this research would contribute significantly to the existing applicable literature on clawbacks using a qualitative approach.…”
Section: Introductionmentioning
confidence: 99%